Fairness Properties of Compensation Schemes - Christoph Becker; Dietmar Fehr; Hannes Rau; Stefan T. Trautmann; Yilong Xu (CESifo GmbH, 2025)
How do different characteristics of pay-for-performance schemes affect fairness perceptions? In two studies, we systematically consider three major classes of incentive schemes: continuous piece rate incentives, discrete bonus schemes, and tournament incentives. We find that pay inequality has a strong negative effect on perceived fairness. Controlling for pay inequality, people consider piece rate schemes fairer than those with a discrete bonus and a tournament design in particular. Adding performance-dependent resource advantages or handicaps negatively influences perceived fairness. We find that procedural fairness judgments are an important factor influencing overall judgments and demonstrate in a third study that the latter have relevant behavioral consequences.
Keywords: C90; D63; J31; J41; 330; incentives; merit; contract design; fairness; inequality